Exploring EFL University Students’ Experiences of Engaging with ChatGPT-Generated Feedback during Academic Writing: A Qualitative Case Study - Ryan Purnomo Ryan; Moh Rif'attullah Rif'attullah; Septiana Wandira Septiana; Thomas Kaufmann Thomas; Deng Zhauyue Deng; A'i Mulyani Az-Zahra Mulyani (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background: This study investigates how EFL university students engage with ChatGPT-generated feedback during academic writing, focusing on behavioral, cognitive, and affective dimensions. Although generative AI is  increasingly used as a feedback tool in EFL contexts, limited research has examined how students interpret, evaluate, and respond to AI-generated feedback as part of the writing process. Methodology: This qualitative case study involved five EFL university students who had experience using ChatGPT as a feedback tool during academic writing tasks. Data were collected through semi-structured interviews exploring students’ reported experiences, perceptions, and decision-making processes when interacting with ChatGPT-generated feedback. The interview data were analyzed thematically to identify perceived behavioral, cognitive, and affective dimensions of AI-mediated feedback engagement. Findings: The findings suggest that participants reported engaging with ChatGPT-generated feedback through iterative revision, evaluative judgment, and emotional regulation, reflecting behavioral, cognitive, and affective dimensions of feedback engagement. Participants also perceived several affordances of ChatGPT, including immediate responses, explanatory support, and motivational encouragement, while simultaneously reporting challenges related to feedback accuracy, contextual appropriateness, and potential overreliance. These findings indicate that the pedagogical value of AI-generated feedback is not inherent in the technology itself but may emerge through learners’ critical interpretation, evaluation, and adaptation of AI suggestions during the revision process. Originality: This study provides qualitative insights into EFL students’ engagement with AI-generated feedback by examining their self-reported experiences of interacting with ChatGPT during academic writing revision. The findings reveal how students perceived behavioral, cognitive, and affective dimensions of engagement, including their reported practices of seeking, evaluating, and applying AI-generated feedback, as well as their emotional responses toward AI-assisted writing. Rather than providing direct evidence of students’ revision processes, this study offers an in-depth understanding of how learners interpret and negotiate ChatGPT feedback within their academic writing experiences.